Psychosocial Factors and Risk of Incident Heart Failure: The Multi-Ethnic Study of Atherosclerosis. (January 2016) - Ogilvie, Rachel P.; Everson-Rose, Susan A.; Longstreth, W.T.; Rodriguez, Carlos J.; Diez-Roux, Ana V.; Lutsey, Pamela L.
Abstract : Background—: Heart failure (HF) is a major source of morbidity and mortality in the United States. Psychosocial factors have frequently been studied as risk factors for coronary heart disease but not for HF. Methods and Results—: We examined the relationship between psychological status and incident HF among 6782 individuals from the Multi-Ethnic Study of Atherosclerosis (MESA). Anger, anxiety, chronic stress, depressive symptoms, and hostility were measured using validated scales, and physician reviewers adjudicated incident HF events. Cox proportional hazards models were used to adjust for relevant demographic, behavioral, and physiological covariates. Interactions by age, race, sex, and self-reported health were examined in exploratory analyses. During a mean follow-up of 9.3 years, 242 participants developed incident HF. There was no association between psychosocial factors and HF hazard ratios (95% confidence interval) for the highest versus lowest quartile: anger=1.14 (0.81–1.60), anxiety=0.74 (0.51–1.07), chronic stress=1.25 (0.90–1.72), depressive symptoms=1.19 (0.76–1.85), and hostility=0.95 (0.62–1.42). In exploratory analysis, among the participants reporting fair/poor health at baseline, those reporting high versus low levels of anxiety, chronic stress, and depressive symptoms had 2-fold higher risk of incident HF, but there was no association for those with good/very good/excellent self-reported health. Conclusions—: Overall, these psychosocial factors were not significantly associated with incident HF. However, for participants reporting poor health at baseline, there was evidence that anxiety, chronic stress, and depressive symptoms were associated with increased risk of HF. Future research with greater statistical power is necessary to replicate these findings and seek explanations.